RACE, GENDER AND AGE VARIABILITY ON HUMAN VISION SENSITIVITY: A STUDY FOR LIMITED MALAYSIAN POPULATION - Saptari, Adi; Ebrahim, Zuhriah; Saleh, Mohd. Rizal (Journal of Human Capital Development (JHCD), 2010)
Human vision sensitivity in this study referring to Critical Flicker-Fusion (CFF) threshold and Fusion-Flicker threshold for limited Malaysian population. The study investigates variability of race, gender and age for CFF threshold. There are three main ethnic groups or races in Malaysia namely Melayu, Chinese and Indian. 233 respondents female and male, young and adult are participated ranging from age 8 to 60+ years. The study found out that the CFF for limited Malaysian population is 36.01 Hertz, and for young age is 32.31 Hertz and adult is 37.57 Hertz. There is not any evidence the CFF is significantly different between adult female and male. However, there is a significant different between young people and adult. No significant differences in CFF with regards to races. Keywords: critical flicker fusion, age, race, gender